1982
DOI: 10.1093/ajcn/35.1.127
|View full text |Cite
|
Sign up to set email alerts
|

The effects of oral iodized oil on intelligence, thyroid status, and somatic growth in school-age children from an area of endemic goiter

Abstract: One hundred goitrous school children received 475 mg iodized oil by mouth, while 100 controls received mineral oil, on a double-blind basis. On follow-up 22 months later the urinary iodine had increased and goiter size had decreased in both groups, more strikingly in the iodine-treated children. There were no consistent differences between the two treatment groups in rate of somatic growth or performance on the Stanford-Binet and Bender tests. Because of the complexities introduced by increases in urinary iodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0
3

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(67 citation statements)
references
References 15 publications
4
60
0
3
Order By: Relevance
“…Thyroid size was reduced by nearly half at 30 and 50 weeks and the goiter rate fell to near 10%. This reduction in goiter prevalence is more pronounced than those described by most previous authors (Bautista et al, 1982;Zitai, 1983;Eltom et al, 1985;Dunn, 1987;Benmiloud et al, 1994;Furne Âe et al, 1995), but because of varying conditions in these studies (age of subjects, severity of iodine de®ciency, geographic location, ultrasound vs palpation for goiter grading, follow-up intervals), it is dif®cult to compare results. In an area of endemic goiter in the Sudan, 200 mg of iodine as iodized oil reduced goiter prevalence as measured by palpation by 60% at 1 y (Elnager et al, 1995).…”
Section: Discussionmentioning
confidence: 59%
“…Thyroid size was reduced by nearly half at 30 and 50 weeks and the goiter rate fell to near 10%. This reduction in goiter prevalence is more pronounced than those described by most previous authors (Bautista et al, 1982;Zitai, 1983;Eltom et al, 1985;Dunn, 1987;Benmiloud et al, 1994;Furne Âe et al, 1995), but because of varying conditions in these studies (age of subjects, severity of iodine de®ciency, geographic location, ultrasound vs palpation for goiter grading, follow-up intervals), it is dif®cult to compare results. In an area of endemic goiter in the Sudan, 200 mg of iodine as iodized oil reduced goiter prevalence as measured by palpation by 60% at 1 y (Elnager et al, 1995).…”
Section: Discussionmentioning
confidence: 59%
“…Notably, in the only two of the above studies that analyzed results by gender, cognitive improvements were only found among girls, although in both cases the findings were merely suggestive given limited sample sizes (Bautista et al, 1982;Shrethsa, 1994). Consistent with this pattern, practitioners have noted that adolescent IDD, including rates of goiter and average severity among sufferers, is systematically higher among females (Allen and Gillespie, 2001;Simon et al, 1990).…”
Section: B Gender Differences In Iodine Deficiencymentioning
confidence: 95%
“…As a result, even mild maternal iodine deficiency is now hypothesized to reduce intelligence quotients by a noticeable margin. 5 While there have been no experimental or large-scale observational studies of the cognitive effects of moderate iodine deficiency in humans, there is suggestive but mixed evidence from community-based assessments of iodine intervention trials that supplementation can improve performance on cognitive tests (Bleichrodt et al, 1994;Bautista et al, 1982). One oft-cited study in Ecuador found a 10-15 point difference in IQ between 50 offspring of women given iodine prophylaxis in early pregnancy compared with children in untreated communities (Shrethsa, 1994).…”
Section: A Iodine Deficiencymentioning
confidence: 99%
“…A number of intervention studies have been carried out in children ranging in age from 5 to 12 years. Two studies in Bolivia [68] and Bangladesh [99] did not show any effect, while two in Malawi [59] and Benin [100] Fig. 7.…”
Section: R E V I S E Smentioning
confidence: 95%